INTEGRAL MEAN ESTIMATE FOR POLYNOMIALS WITH RESTRICTED ZEROS - N. A. Rather; N. Wani; A. Bhat (Проблемы анализа)
In this paper, we present certain sharp 𝐿^𝑝-inequalities for polynomials with restricted zeros. Our results improve and generalize some known integral inequalities for polynomials in the complex domain.